The kids' karate workbook: : a take-home training guide for young martial artists - Goodman, Didi; Nikaya, Linda (Berkeley, Calif. : Blue Snake Books, 2009)
'A take-home workbook for young students of Karate and Taekwondo, complete with puzzles, tests, and training exercises to do alone or with a friend'--Provided by publisher
Keywords: Karate -- Training; Tae kwon do -- Training